2016
DOI: 10.1002/jctb.5007
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient bioconversion of methane to methanol using a novel type I Methylomonas sp. DH‐1 newly isolated from brewery waste sludge

Abstract: Background Methane is the major component of natural and shale gas. Methane can be converted into methanol via a bioprocess using methanotrophs, and methanol is a valuable chemical feedstock for the production of value‐added chemicals. This work demonstrates highly effective bioconversion of methane to methanol using a newly isolated novel methanotroph, Methylomonas sp. DH‐1. Results A novel methanotroph strain was isolated from activated sludge from a brewery plant and characterized using phylogenetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…To evaluate the feasibility of the SFR system for methane conversion and to investigate the mass transfer characteristics of the system using the gas containing air and methane, the mass transfer coefficients for each gas were determined at various liquid flow rates. A mixed gas composed of 30% methane and 70% air, which is commonly used for the bioconversion of methane [5], was supplied to the system as feed gas. Although there were some fluctuations-possibly caused by a disturbance in the measurement of dissolved methane by the gas chromatography, owing to the presence of impurities including air in the sample tube (see Section 4.2 for the detailed method of measurement)-the k L a values were similar to those obtained in the cases using single-component gas (Figure 3b).…”
Section: Improvement Of Mass Transfer Performance By Using Hydrophilimentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the feasibility of the SFR system for methane conversion and to investigate the mass transfer characteristics of the system using the gas containing air and methane, the mass transfer coefficients for each gas were determined at various liquid flow rates. A mixed gas composed of 30% methane and 70% air, which is commonly used for the bioconversion of methane [5], was supplied to the system as feed gas. Although there were some fluctuations-possibly caused by a disturbance in the measurement of dissolved methane by the gas chromatography, owing to the presence of impurities including air in the sample tube (see Section 4.2 for the detailed method of measurement)-the k L a values were similar to those obtained in the cases using single-component gas (Figure 3b).…”
Section: Improvement Of Mass Transfer Performance By Using Hydrophilimentioning
confidence: 99%
“…However, the current conversion approach, which employs the Fischer-Tropsch process, still faces several obstacles preventing its commercialization owing to its high capital requirements and energy-intensive nature [1,4]. The aerobic bioconversion of methane-the main component of natural gas-by using methanotrophic microorganisms as biocatalysts has shown good potential as an alternative to the Fischer-Tropsch process due to its high selectivity, ambient operating temperature, one-step direct process, and reduced technological complexity [1,[4][5][6][7]. Therefore, it can be applied to monetize small sources of natural gas, such as stranded and flared natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…; Hur et al . ). These results indicated that the methanol tolerance abilities of methanotrophs are far than they were predicted.…”
Section: Introductionmentioning
confidence: 97%
“…Some methanotrophs were domesticated for methanol utilization, but the performances of the domesticated strains were not stable (Koffas et al 2003). Recently, some new isolated methanotrophs were reported to tolerate methanol concentration as high as 40-56 g l À1 (Eshinimaev et al 2002;Dunfield et al 2003;Hur et al 2017). These results indicated that the methanol tolerance abilities of methanotrophs are far than they were predicted.…”
mentioning
confidence: 97%
“…Recently, the type l Methylomonas sp. DH-1 was isolated from brewery waste sludge, and several engineering tools have been developed [18]. This bacterium has been favored in diverse examples of metabolic engineering: the conversion of methane to methanol [18] and the production of value-added chemicals such as acetone [19,20], succinate [21], and D-lactate [22].…”
Section: Introductionmentioning
confidence: 99%